Debugging and testing Android applications : discover effective techniques for diagnosing, isolating, and fixing problems - Stanley, Chris (O'Reilly, 2016)
"In this Debugging and Testing Android Applications training course, expert author Chris Stanley will teach you how to effectively diagnose, isolate, and fix problems in Android applications. This course is designed for the absolute beginner, meaning no previous experience with debugging Android applications is required. You will start by learning about passive debugging, including logging by severity, Android log analysis, and slow performance. From there, Chris will teach you how to configure an Android virtual machine, attach to devices, and inspect data. Finally, this video tutorial will teach you about passive inspection tools and Android unit testing. Once you have completed this computer based training course, you will have learned how to effectively debug and test Android applications."--Resource description page.